A Meta-Analysis Comparing the Effectiveness of Uterine-Sparing Procedures versus Hysterectomy for Adenomyosis: Patient-Reported Outcomes and Fertility Preservation - Pradnyana, I Wayan Agus Surya; Kadek Agus Wijaya (HM Publisher, 2025)
Background: Adenomyosis is a benign gynecological condition that can cause significant morbidity, including dysmenorrhea, menorrhagia, and pelvic pain. Hysterectomy has been the traditional treatment for adenomyosis, but uterine-sparing procedures (USPs) are increasingly being considered, especially for women who desire fertility preservation. This meta-analysis compared the effectiveness of USPs versus hysterectomy for adenomyosis, focusing on patient-reported outcomes (PROs) and fertility preservation. Methods: A systematic search of PubMed, Embase, and Cochrane Library databases was conducted for studies published between 2013 and 2024, comparing USPs (e.g., laparoscopic or hysteroscopic adenomyomectomy, uterine artery embolization) with hysterectomy for adenomyosis. Studies reporting PROs (dysmenorrhea, menorrhagia, pelvic pain, quality of life) and fertility outcomes (pregnancy rate, live birth rate) were included. Random-effects models were used to pool data and assess heterogeneity. Results: Six studies (n = 1248 patients) met the inclusion criteria. USPs were associated with significantly lower rates of major complications (odds ratio [OR] 0.35, 95% confidence interval [CI] 0.23-0.54, p<0.0001) and shorter hospital stays (mean difference -2.73 days, 95% CI -3.29 to -2.17, p<0.0001) compared to hysterectomy. PROs, including dysmenorrhea, menorrhagia, and pelvic pain, significantly improved in both groups, with no significant difference between USPs and hysterectomy. Fertility preservation was significantly higher in the USP group (OR 3.9, 95% CI 3.02-5.03, p<0.0001). Conclusion: USPs offer a safe and effective alternative to hysterectomy for adenomyosis, with comparable improvements in PROs and significantly higher rates of fertility preservation. This information can guide clinicians and patients in shared decision-making regarding the optimal treatment approach.